Optimizing the Performance of the Satreskrim Pidum Unit to Improve the Resolution of Motor Vehicle Theft Crimes in the Legal Area of the Lamongan Police - Nugroho, Nicholas Diva (Advances in Police Science Research Journal, 2024)
Motorcycle theft was the most common criminal offense in 2022 in the jurisdiction of the Lamongan District Police. The Indonesian National Police, particularly the Criminal Investigation Unit (Satreskrim), is tasked with effectively and optimally resolving criminal acts to ensure public safety and order. This research aims to explain the performance of the Satreskrim's Unit Pidum members and the management process in uncovering motorcycle theft crimes in the Lamongan District Police area to enhance the resolution of such crimes through cooperation. The study adopts a qualitative approach using a case study method. Data were obtained from interviews, observations, and document analysis. The study found that the suboptimal performance of Satreskrim is influenced by various factors, including limited personnel (in terms of quality and quantity), suboptimal budget utilization, inadequate facilities and equipment, ineffective methods, lack of coordination with relevant agencies and the community, and suboptimal organizational management. Therefore, improvement measures are necessary to optimize Satreskrim's performance.